Association between Active Cancer and Risk of Thrombotic and Cardiovascular Outcomes in Outpatients with COVID-19: A CORONA-VTE Network Analysis - McGonagle, Bridget; Greason, Christie; Krishnathasan, Darsiya; Scimeca, Giovanni; Bejjani, Antoine; Khairani, Candrika D.; Hamade, Nada; Sato, Alyssa; Leyva, Hannah; Campia, Umberto; Davies, Julia; Porio, Nicole; Assi, Ali A.; Armero, Andre; Tristani, Anthony; Ortiz-Rios, Marcos D.; Nauffal, Victor; Almarzooq, Zaid; Wei, Eric; Zuluaga-Sánchez, Valeria; Zarghami, Mehrdad; Achanta, Aditya; Jesudasen, Sirus J.; Tiu, Bruce C.; Merli, Geno J.; Leiva, Orly; Fanikos, John; Sharma, Aditya; Rizzo, Samantha; Pfeferman, Mariana B.; Morrison, Ruth B.; Vishnevsky, Alec; Hsia, Judith; Nehler, Mark R.; Welker, James; Bonaca, Marc P.; Carroll, Brett J.; Goldhaber, Samuel Z.; Lan, Zhou; Bikdeli, Behnood; Piazza, Gregory (TH Open, 2025)
Coronavirus disease 2019 (COVID-19) and active cancer are each independently associated with excess risk of thrombotic and cardiovascular events. However, data are limited regarding the risk of these events in outpatients with active cancer and concomitant COVID-19.This study aimed to retrospectively examine the association between active cancer and thrombotic and cardiovascular outcomes among non-hospitalized patients with COVID-19.Data from the outpatient cohort with confirmed COVID-19 from the 10,420-patient multicenter U.S. CORONA-VTE Network registry were used. Active cancer was defined as having a malignancy diagnosis (excluding non-melanoma skin cancer) or receiving cancer-related treatment within the past year. Outcomes were independently adjudicated and included a composite of venous and arterial thromboembolism, and a composite of major adverse cardiovascular events, including thromboembolism, heart failure, myocarditis, new atrial fibrillation, and cardiovascular death within 90 days of COVID-19 diagnosis.The registry included 6,576 outpatients, of whom 166 (2.5%) had active cancer (mean age 61 ± 16, 53% female). For outpatients with and without active cancer, the 90-day cumulative incidences of thromboembolism after developing COVID-19 were 4.2% and 1.2%, respectively (hazard ratio [HR]: 3.65; 95% confidence interval [CI]: 1.73–7.69, p < 0.001). Corresponding 90-day cumulative incidences of cardiovascular events were 5.4% and 1.9% (HR: 2.97; 95% CI: 1.46–6.05, p = 0.003). In adjusted analyses, non-hospitalized patients displayed an increased risk of thrombotic outcomes (HR: 2.48, 95% CI: 1.13–5.45, p = 0.024) but not cardiovascular outcomes (HR: 1.76, 95% CI: 0.85–3.62, p = 0.13).Outpatients with COVID-19 and active cancer demonstrated an increased hazard of thrombotic events compared with outpatients without cancer.
Keywords: cancer; cardiovascular events; COVID-19; deep vein thrombosis; pulmonary embolism